Implikasi Teori Belajar Kognitif Dalam Proses Pengembangan Karakter di Sekolah Dasar Melalui Mata Pelajaran Bahasa Indonesia - Ramadhani, Dini Ashri; Pauziyyah, Afifah Intan; Nurharini, Atip; Putri, Dinasti Sekar; Azizi, Kurniawan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The use of cognitive learning theory in the learning process in elementary schools, especially in Indonesian subjects that involve the use of learning methods and media that can stimulate students' cognitive development. One effective medium in this context is the flannel board. This study aims to describe the implications of cognitive learning theory in character development in elementary schools through Indonesian subjects. The method applied in this study is a qualitative research method that relies on a library research approach. Information is obtained through classroom observation, interaction with teachers, and evaluation of data from Indonesian learning materials presented through flannel boards. Cognitive learning theory, especially the concepts of reasoning, memory, and problem solving, became the basis of analysis to evaluate the effectiveness of the use of flannel boards in developing character to stimulate the learning process of students. The results of this research show that the use of flannel boards in the learning process in elementary schools can make a positive contribution to students' cognitive development. Through the organization of structured and visual learning materials, flannel boards can improve students' memory capacity. In addition, the active interaction of students with the flannel board allows the development of reasoning and problem-solving abilities. In the context of implementing cognitive learning theory, teachers can utilize flannel boards as aids to present information concretely, facilitate knowledge construction, and encourage students' active participation in learning. The implications of this study provide the basis for the development of more effective learning strategies at the primary school level, by harnessing the potential of flannel boards as a learning medium that stimulates students' cognitive development.